Pelatihan Pembuatan Hand Sanitizer dari Bahan Dapur pada Masyarakat Desa Gabusbanaran - Muhammad Farid Nasrulloh; Ospa Pea Yuanita Meishanti; Ailam Oktadawiyah Alfaniah; Yusrotul Maghfiroh; Wisnu Siwi Satiti; Ino Angga Putra (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Hand sanitizer is one of the antiseptic ingredients in the form of a gel that is often used by many people as a practical hand washing medium. Hand sanitizer can be used anytime and anywhere, for example after handling money, before eating, after using the toilet and after taking out the trash. Partner problems in this activity are (1) partners do not know about the importance of preventing the spread of the Corona Virus (Covid-19) and implementing health protocols. (2) partners do not yet know the benefits and use values ​​of betel leaf plants, kaffir lime leaves, lime juice and lemongrass stalks as natural hand sanitizers. (3) lack of knowledge and skills of partners regarding the manufacture of this natural hand sanitizer. The purpose of this activity is as follows (1) to educate the public about the importance of preventing the spread of the Corona Virus (Covid-19) and implementing health protocols. (2) to increase the use value of betel leaf plants, kaffir lime leaves, lime juice and lemongrass stalks as natural hand sanitizers. (3) to improve the knowledge and skills of the community as well as to improve the community's economy during the pandemic. This service uses the Asset Based Community Development (ABCD) approach. The ABCD approach is an approach that leads to an independent and maximum understanding and internalization of assets, strengths, potential, and utilization. The conclusion obtained from this service activity is that there is an increase in the knowledge and skills of the Gabusbanaran Village community about how to make hand sanitizers from natural ingredients so that they can reduce additional costs for purchasing hand sanitizer products themselves in tackling the spread of Covid-19.